The Effect of Different Feeding on The Growth and Colour Brightness of Glofish - Dewi, Aisah Mustika; Rostika , Rita; Priowirjanto, Gatot Hari; Zidni, Irfan (LifeSciFi, 2025)
This study aims to evaluate the effectiveness of different types of feed, namely natural the growth and color brightness of GloFish Starfire Red. Achieving optimal color brightness and growth is essential in ornamental fish cultivation, as these factors directly impact the marketability and economic value of the fish. The research employed a Completely Randomized Design (CRD) with four treatments each replicated three times to ensure the validity of results. The parameters measured in this study included absolute weight growth, absolute length increase, and brightness in color. Color brightness was analyzed using a digital visual comparison tool to ensure objective measurement. The findings revealed that natural feed significantly enhanced both weight and length growth when compared to artificial feed. Furthermore, fish that were fed with Chironomidae exhibited a more pronounced improvement in color brightness than those subjected to other treatments. These results suggest that specific types of natural feed may offer superior benefits over artificial feed in promoting both aesthetic and physical development in ornamental fish like Glofish Starfire Red.